Chemical Speciation, Bioavailability and Multi-Index Assessment of Heavy Metal Contamination in Dumpsite-Affected Farmland Soils of Anyigba, Nigeria - Okpanachi, Clifford Baba; Haruna, Jesse; Onoyima, Christian; Attah, Egu Samuel; Abalaka, Edwin; Ameh, Ekwu Mark; Ejukwa, Emmanuel (Journal of Science Research and Reviews, 2025)
This study assessed the physicochemical properties, chemical speciation, and ecological risk of heavy metals in farmland soils near municipal dumpsites in Anyigba, Nigeria. The soils were slightly acidic (pH 5.2–6.4), with moderate organic matter (1.82–2.65%) and cation exchange capacity (7.4–12.3 cmol/kg), while electrical conductivity was low (92–148 µS/cm), indicating non-saline conditions that promote metal mobility. Heavy metals occurred in the ranges: Cd (4.60–5.91 mg/kg), Cu (5.81–12.44 mg/kg), Ni (11.70–18.92 mg/kg), Cr (4.93–8.17 mg/kg), and Pb (3.99–6.25 mg/kg). Speciation analysis showed Cd concentrated in exchangeable and carbonate fractions (45–58%), reflecting high mobility; Cu was mainly bound to organic matter (40–52%); Ni dominated reducible fractions (35–48%); Cr occurred in the residual fraction (55–68%); and Pb partitioned into carbonate and reducible fractions (30–45%). Contamination factors (CF) indicated very high Cd contamination (6.0–7.5), moderate Ni (2.0–3.0), Cu (1.2–2.1), and Pb (1.1–1.8), and low Cr (0.8–1.4). The Pollution Load Index (PLI) ranged 1.2–2.0, confirming overall deterioration, while the Nemerow Pollution Index (NPI) of 2.4–3.1 signaled considerable pollution risk. Ecological Risk Index (ERI) values highlighted Cd as the major contributor (60–70% of total risk), with individual ERI of 180–220, categorizing it as a “considerable ecological risk.” In contrast, Cu, Ni, Cr, and Pb presented low to moderate risks (ERI < 40). Integration of soil properties with speciation data indicated that acidic pH and relatively low organic matter enhanced Cd solubility and bioavailability, whereas organic complexation stabilized Cu. These results demonstrate that ecological assessments must consider both total concentrations and chemical forms of metals. Recommended interventions include phytoremediation, soil organic amendments, and stricter waste management to mitigate contamination and ensure sustainable agriculture in Anyigba.